Elementary properties of Ca2+ channels and their influence on multivesicular release and phase-locking at auditory hair cell ribbon synapses - Magistretti, Jacopo; Spaiardi, Paolo; Johnson, Stuart L.; Masetto, Sergio (Frontiers in Cellular Neuroscience, 2015)
Voltage-gated calcium (Cav1.3) channels in mammalian inner hair cells (IHCs) open in response to sound and the resulting Ca2+ entry triggers the release of the neurotransmitter glutamate onto afferent terminals. At low to mid sound frequencies cell depolarization follows the sound sinusoid and pulses of transmitter release from the hair cell generate excitatory postsynaptic currents (EPSCs) in the afferent fibre that translate into a phase-locked pattern of action potential activity. The present article summarises our current understanding on the elementary properties of single IHC Ca2+ channels, and how these could have functional implications for certain, poorly understood, features of synaptic transmission at auditory hair cell ribbon synapses.